Portrait of Wilhelm Ostwald, 1903 (1903)
Picture postcard sent to Rosa Bredig (1877-1933) from her husband, Georg Bredig (1868-1944). The black and white photograph features a portrait of Wilhelm Ostwald (1853-1932) wearing a hat. Ostwald was a German chemist and philosopher. In 1909, he received the Nobel Prize in Chemistry for his work on catalysis and for his investigations into the fundamental principles governing chemical equilibria and rates of reaction. Ostwald, along with Jacobus Henricus van 't Hoff (1852-1911), Walther Nernst (1864-1941), and Svante Arrhenius (1859-1927), is considered one of the founding fathers of the field of physical chemistry. When he retired in 1906, Ostwald studied art, philosophy, and politics.
Keywords: Ostwald, Wilhelm, 1853-1932; Bredig, Rosa, 1877-1933; Chemists; Nobel Prize winners; Bredig, Georg, 1868-1944